Taboo in Balinese Language Spoken in Sesetan Village: A Descriptive Qualitative Study - Aryasuari, Putu Tanniya Pradnyan; Budasi, I Gede; Juniarta, Putu Adi Krisna (Journal of Linguistic and Literature Studies, 2024)
This research focused on taboo words in connection with Tri Hita Karana concept. The objectives of the study are: to find out the taboo words, to find out the taboo forms, and to find out their references in Balinese language spoken in Sesetan Village. The research was designed in the form of a descriptive qualitative study. The main informant is Prajuru desa adat. The first secondary informant is Mangku dadya and the second secondary informant is Kelian desa adat. The other additional instruments were interview guide. The technique of collecting data was by an in-depth interview. The obtained data were analysed using the procedures suggested by Miles, Huberman and Saldana (2014). The results of the study were as follows: 1) There were 30 Taboo words in Balinese language spoken in Sesetan Village. They were group into 3 domains within the Tri Hita Karana concept. 3 words exist in Parahyangan; 26 words exist in Pawongan; and 1 word exist in Palemahan. 2) There are 20 words related to taboo forms included 15 words related to taboo names and words, and 5 words related to taboo on swearing words. 3) There were 11 references of taboo.